2019
DOI: 10.1042/bcj20180440
|View full text |Cite
|
Sign up to set email alerts
|

lncRedibly versatile: biochemical and biological functions of long noncoding RNAs

Abstract: Long noncoding RNAs (lncRNAs) are transcripts that do not code for proteins, but nevertheless exert regulatory effects on various biochemical pathways, in part via interactions with proteins, DNA, and other RNAs. LncRNAs are thought to regulate transcription and other biological processes by acting, for example, as guides that target proteins to chromatin, scaffolds that facilitate protein–protein interactions and complex formation, and orchestrators of phase-separated compartments. The study of lncRNAs has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 234 publications
(266 reference statements)
0
33
0
Order By: Relevance
“…lncRNAs are involved in numerous physiological processes, including cell growth, proliferation, apoptosis, migration and differentiation (17)(18)(19). The normal expression of lncRNA is necessary to maintain cell homeostasis and function, and its aberrant expression is closely associated with a variety of diseases, including cancer (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are involved in numerous physiological processes, including cell growth, proliferation, apoptosis, migration and differentiation (17)(18)(19). The normal expression of lncRNA is necessary to maintain cell homeostasis and function, and its aberrant expression is closely associated with a variety of diseases, including cancer (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, lncRNAs are thought to be RNAs that have no biologically function. However, subsequent studies have shown that lncRNAs play important roles in transcriptional, post‐transcriptional, and epigenetic processes . LncRNA has a structure similar to mRNA and has a promoter structure and a polyA tail .…”
Section: Introductionmentioning
confidence: 99%
“…Rs3787016, localizes to the fourth intron of RNA polymerase II polypeptide E (POLR2E) 16 gene, has been investigated by several researchers on its association with cancer risk [16,[30][31][32][33][34][35][36][37].The most important function of LncRNAs is involvement in the transcriptional or posttranscriptional regulation of gene expression [38]. Abnormal expressions of these RNAs facilitate tumor-cell proliferation, invasion and survival in cancer development and progression [39][40][41].…”
Section: Discussionmentioning
confidence: 99%